Connections between Anterior Inferotemporal Cortex and Superior Temporal Sulcus Regions in the Macaque Monkey - Saleem, K. S. (J Neurosci, 2000)
We examined the connections between the anterior inferotemporal cortex and the superior temporal sulcus (STS) in the macaque monkey by injecting Phaseolus vulgaris leucoagglutinin (PHA-L) or wheat germ agglutinin conjugated to horseradish peroxidase (WGA-HRP) into the dorsoanterior and ventroanterior subdivisions of TE (TEad and TEav, respectively) and observing the labeled terminals and cell bodies in STS. We found a clear dichotomy in the connections of the rostral part of STS: the injections into TEad resulted in a dense distribution of labeled terminals and cell bodies in the upper bank of rostral STS, whereas labeling was confined to the lower bank and fundus of rostral STS after injections into TEav. The distribution of labeling in the rostral STS was discontinuous from the distribution of labeling surrounding the injection sites: the lower bank of the rostral STS was spared from labeling in the TEad injection cases, and TEad had only sparse distribution in the TEav injection cases. These results revise the classical view that the lower bank of rostral STS is connected with TE, whereas the upper bank of rostral STS is connected with the parietal, prefrontal, and superior temporal regions (Seltzer and Pandya, 1978, 1991, 1994). The upper bank of the rostral STS is called the superior temporal polysensory area (STP), because it was previously found that neurons there respond to auditory, somatosensory, and visual stimuli. The present results thus suggest that the polymodal representation in STP interacts more with information processing in TEad than TEav. It is also suggested that the information processing in the ventral bank of the rostral STS is distinct from that in TEad, and the former more directly interacts with TEav than TEad.